Online Reviews, Ratings, and Brand Image in Shaping Generation Z’s Purchase Decisions: Evidence from The Originote Consumers in Denpasar - Ni Putu Ayu Candra Wati; Ni Wayan Eka Mitariani; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
The purpose of this study is to analyze how online customer reviews, online customer ratings, and brand image influence purchasing decisions for The Originote products on the TikTok Shop platform. This study focuses on understanding the digital factors that influence consumer behavior, particularly among Gen Z in Denpasar as an active group of social media and e-commerce users. This study employs a quantitative method using non-probability sampling (accidental sampling), involving 112 respondents. The data was collected through a questionnaire distributed to Gen Z customers of The Originote in Denpasar, which had undergone validity, reliability, and classical assumption tests, and was subsequently analyzed using multiple linear regression. The research results demonstrate that online customer reviews, online customer ratings, and brand image significantly contribute to purchasing decisions. This means that the better the customer reviews, the higher the product ratings, and the stronger the brand image perceived by consumers, the more likely they are to purchase The Originote products on TikTok Shop.